Development of gonads and evidence of protogyny in Spangled emperor (Lethrinus nebulosus) from the coastal waters off Negombo, Sri Lanka. - Ranatunga, R. R. M. K. P; Rathnayaka, S. (Sri Lanka J. Aquat. Sci, 2019)
Gonad development and maturation of the spangled emperor Lethrinus nebulosus (Forsskål, 1775) inhabiting coastal waters off Negombo, Sri Lanka was investigated to understand the reproductive strategies. Sexual ontogeny was investigated using histological examinations of the gonads and changes in sex ratio with body size. Cellular characteristics and the most advanced germ cells presented in the gonads were considered for determining the sex and maturity stages. The transitional gonads were characterized by changes in internal gonad structure such as the appearance of spermatocyte and degenerated oocytes in the same developmental stage. Thick strands of stromal tissue within the lamellae and branched secondary strands were observed in transitional individuals. Increased blood vessels and sperm sinuses within the gonad wall were also an indications of sex transition. Therefore, L. nebulosus living in coastal waters off Negombo exhibited an early indication of protogynous hermaphroditism among adults. The sizes at 50% sexual maturity of males and females were estimated to be 29.5 cm and 39.5 cm respectively. A dramatic change in the sex ratio of the adult size classes suggested that female to male sex transition observed between 28.5- 40.4 cm body sizes. Sex ratios were 1.23: 0.46: 1 for female: transitional: males indicating slightly female-biased overall sex ratios. Female dominance in smaller size classes and male dominance in larger size classes were also evident Mean size at first capture recorded for L. nebulosus (19.6 cm) was well below the mean sizes of maturity for both male and female. Size-speciﬁc differences in sex ratios and reproductive potential indicate that conventional regulations that impose size limits for capture would not be very effective for the management of L. nebulosus.
Keywords: Spangled emperor, Lethrinus nebulosus, Maturation, Gonad development, Protogynous hermaphroditism, Sex transition